1997
DOI: 10.1017/s0047404500019497
|View full text |Cite
|
Sign up to set email alerts
|

Communication of respect in interethnic service encounters

Abstract: Divergent practices for displaying respect in face-to-face interaction are an ongoing cause of tension in the US between immigrant Korean retailers and their African American customers. Communicative practices in service encounters involving Korean customers contrast sharply with those involving African American customers in 25 liquor store encounters that were videotaped and transcribed for analysis. The relative restraint of immigrant Korean storekeepers in these encounters is perceived by many African Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(65 citation statements)
references
References 8 publications
1
61
1
2
Order By: Relevance
“…In addition, there was evidence of in/outgroup difference in greeting and thanking behaviour because the Chinese service providers in the study were more inclined to greet and thank non-Chinese customers than Chinese customers. Explicit verbal greetings or closings also do not occur in every service encounter in Bailey's (2001) study on service encounters involving African American and Korean customers in a convenience store operated by immigrant Koreans in California. Bailey reported that the interactions with the 13 Korean customers were shorter whereas the interactions with the 12 African American customers had interpersonal involvement.…”
Section: High-and Low-context Culturesmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, there was evidence of in/outgroup difference in greeting and thanking behaviour because the Chinese service providers in the study were more inclined to greet and thank non-Chinese customers than Chinese customers. Explicit verbal greetings or closings also do not occur in every service encounter in Bailey's (2001) study on service encounters involving African American and Korean customers in a convenience store operated by immigrant Koreans in California. Bailey reported that the interactions with the 13 Korean customers were shorter whereas the interactions with the 12 African American customers had interpersonal involvement.…”
Section: High-and Low-context Culturesmentioning
confidence: 98%
“…Other researchers who have focused on the staging of service encounters have primarily studied the omission of opening and closing stages in interactions between Asian customers and service providers (e.g., Bailey 2001;Kong 1998;Kuang et al 2011;Liu 2009;Pan 2000;Ting et al 2012), and interpreted the omissions as lack of politeness in instrumental exchanges. This interpretation is reasonable given that other researchers have found elaborate sequences for politeness in other settings.…”
Section: Introductionmentioning
confidence: 99%
“…Once the necessary information was gathered, the call-taker responded to the reason for the call, as shown at line 9 in example (3) and at line 12 in example (4). In both sets of calls, apologizing work started at the beginning of the business exchange (Bailey 1997). Call-takers responded to the reason for the call with the second pair part of the adjacency pair initiated by the caller in the second turn of the call, as shown in lines 2 and 9 in (3) and lines 2 and 12 in (4), respectively.…”
Section: Initial Sequencesmentioning
confidence: 99%
“…In both data sets, apologies were initiated at the beginning of the business exchange (Bailey 1997), following the opening sequence and contingency questions. The opening sequence consisted of the production of a multiunit turn with two and three turn-constructional units : organizational identification followed by a greeting, as illustrated at line 1 in example (1), and in some of the CSC calls this was followed by self-identification, as shown at line 1 in example (2).…”
Section: Initial Sequencesmentioning
confidence: 99%
“…Bailey (1997Bailey ( , 2000, for example, analyzes service encounters between Korean retailers and African-American customers to help throw light on the longstanding conflict between these two groups that had been widely reported in the media. Analyzing video recordings of the service encounters, he found that there were noticeable differences in the ways that Korean and African-American customers interacted with the Korean retailers, such as in terms of length of the encounter, overall quantity of talk, inclusion of personable topics and small talk, and the amount of affect displayed.…”
Section: Conflict and Discourse Researchmentioning
confidence: 99%